1998
DOI: 10.1007/bf02770835
|View full text |Cite
|
Sign up to set email alerts
|

Hepatitis TT virus infection in high-risk groups

Abstract: The novel hepatitis TT virus first described by a Japanese group has been reported to be parenterally transmitted and furthermore, to have been detected in patients with hepatitis of unknown etiology. Hence, in the present study its prevalence was investigated within groups at high risk for contracting blood-borne viruses, such as individuals with chronic liver disease, intravenous drug users and recipients of blood and blood products, as compared to voluntary blood donors and pregnant women. To that end, DNA … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
21
0
1

Year Published

2000
2000
2016
2016

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 29 publications
(23 citation statements)
references
References 9 publications
1
21
0
1
Order By: Relevance
“…The comparable prevalence rates among CLD patients and voluntary blood donors suggest that TTV may not be pathogenic in most infected individuals, confirming observations from the United Kingdom (14), Taiwan (8), and recently, Japan (10). However, these observations are in contrast to other reports from Japan (17), the United States (3), and Thailand (19). Interestingly, none of the 21 HBV DNAand HCV RNA-negative CLD patients were TTV DNA positive.…”
Section: A5427 (5ј-tac Cay Tta Gct Ctc Tat Tct Wa-3ј)supporting
confidence: 85%
“…The comparable prevalence rates among CLD patients and voluntary blood donors suggest that TTV may not be pathogenic in most infected individuals, confirming observations from the United Kingdom (14), Taiwan (8), and recently, Japan (10). However, these observations are in contrast to other reports from Japan (17), the United States (3), and Thailand (19). Interestingly, none of the 21 HBV DNAand HCV RNA-negative CLD patients were TTV DNA positive.…”
Section: A5427 (5ј-tac Cay Tta Gct Ctc Tat Tct Wa-3ј)supporting
confidence: 85%
“…Similar prevalences of TTV have been reported in pregnant women and unselected blood donors in Thailand. 41 Thus, the high prevalence of TTV viremia in pregnant Gabonese women probably reflects extensive exposure of the general population in this area. As there is currently no serological assay for TTV infection, we were only able to investigate active TTV infection.…”
Section: Discussionmentioning
confidence: 99%
“…McDonald et al (89) and Poovorawan et al (135) reported that, in contrast to hepatitis B and C, the frequency of TTV infection in individuals at high risk for sexually transmitted diseases was not particularly high. Together with other findings (26,55,105), this suggests that sexual transmission plays an unimportant role, if any.…”
Section: Epidemiologymentioning
confidence: 99%